Mengukur Keberhasilan Penyampaian Materi Fiqih di Madrasah Ibtidaiyah : Review Kepustakaan: Measuring the Success of Fiqh Delivery in Madrasah Ibtidaiyah: A Literature Review - Johan, Masyitoh (COSMOS : Jurnal Ilmu Pendidikan, Ekonomi dan Teknologi, 2024)
This research examines the successful delivery of fiqh materials in Madrasah Ibtidaiyah through a literature review. Recognizing that fiqh education plays an important role in shaping good religious understanding and practice among students, this study evaluates the various teaching methods and approaches that have been implemented. Through an extensive literature review, it identifies factors that influence the effectiveness of the teaching and learning process, such as teachers' qualifications, teaching materials, teaching methods, and students' motivation and learning environment. It seeks to provide an overview of best practices that can be adopted to improve the quality of fiqh delivery, as well as challenge traditional practices that may no longer fit the needs and challenges of the times. In a friendly and empathetic way, the study leads to practical recommendations that aim to support Madrasah Ibtidaiyah teachers in optimizing the teaching and learning process. The ultimate goal is to ensure that students not only understand fiqh material theoretically, but are also able to apply it in their daily lives, educating and empowering them as individuals with noble character.